2016
DOI: 10.1080/14737140.2016.1229600
|View full text |Cite
|
Sign up to set email alerts
|

Immunological effects of chemotherapy and radiotherapy against brain tumors

Abstract: INTRODUCTION The mainstays of brain tumor therapy are surgery, radiotherapy and chemotherapy. Cancer immunotherapy is explored as an additional treatment modality. However, emerging evidence indicates that also radio-and chemotherapy have immunological effects in addition to their cytotoxic and cytostatic activities. AREA COVERED We summarize the literature on radioand chemotherapy-mediated immunological effects in primary and secondary brain tumors and outline open questions within the field. To this end, a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 90 publications
0
26
0
1
Order By: Relevance
“…119,154,[387][388][389] Even beyond the induction of ICD, several chemotherapeutics have been shown to elicit on-target or off-target immunostimulatory doses, especially when employed at low doses and/or according to revisited treatment protocols. [390][391][392][393] As we stand at the apex of the immunotherapy revolution, the immunomodulatory effects of traditional anticancer agents, including chemotherapy, RT and others, can no longer be ignored. Thus, preclinical studies based on immunocompetent models followed by well-designed and highly immunomonitored clinical trials 394 are urgently awaited to identify new doses and treatment schedules that enable maximal immunostimulation by chemotherapy and hence set an optimal stage for combination with ICBs and other forms of immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…119,154,[387][388][389] Even beyond the induction of ICD, several chemotherapeutics have been shown to elicit on-target or off-target immunostimulatory doses, especially when employed at low doses and/or according to revisited treatment protocols. [390][391][392][393] As we stand at the apex of the immunotherapy revolution, the immunomodulatory effects of traditional anticancer agents, including chemotherapy, RT and others, can no longer be ignored. Thus, preclinical studies based on immunocompetent models followed by well-designed and highly immunomonitored clinical trials 394 are urgently awaited to identify new doses and treatment schedules that enable maximal immunostimulation by chemotherapy and hence set an optimal stage for combination with ICBs and other forms of immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…298,304 Nonetheless, a majority of currently available anticancer agents mediate on-target or off-target immunostimulatory effects, which strongly argues against an irrelevant role for the immune system in the therapeutic effects of these treatments. [305][306][307][308] Moreover, in various cases, chemotherapeutics applied through multiple treatment cycles may negatively affect the immune system, by causing lymphopenia or leucopenia, thereby further compromising antitumor immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study showed no improvement in quality of life or overall survival after whole brain radiation therapy for patients with lung-to-brain metastases (Mulvenna et al, 2016). Given the high degree of cytotoxicity of these therapies on healthy brain tissue (Weiss et al, 2016), these findings strongly suggest that supplementation of optimal supportive care with whole brain radiotherapy ought to be reconsidered for the clinical management of brain metastases. Additionally, they indicate that clinical assessment of benefit versus risk in a quantifiable manner is particularly important to minimize additional unnecessary harm to this patient population.…”
Section: Introductionmentioning
confidence: 99%